The study of visible-light photocatalytic degradation activity of Ag doped g-C3N4 obtained by heating process - Xiao Liu; Ru-Yi Tang; Xue-Min Xia; Yao-Yu Qin; Xia Zhang (Materials Research Express, 2020)
In this paper, Ag nanoparticles (Ag NPs) were loaded on pure g-C _3 N _4 (CN) via two different methods of direct heating and indirect heating to form g-C _3 N _4 /Ag-DX and g-C _3 N _4 /Ag-IDX photocatalysts, respectively. Using methylene blue as the degradation dye, the photocatalytic performance of g-C _3 N _4 /Ag-DX and g-C _3 N _4 /Ag-IDX was studied through visible light photocatalysis experiments. The results demonstrated that the photocatalytic performance of g-C _3 N _4 /Ag-DX and g-C _3 N _4 /Ag-IDX both increases with the increase in content of Ag nanoparticles. It is obvious that g-C _3 N _4 /Ag-ID8 has the optimal photocatalytic activity. Meanwhile, the g-C _3 N _4 /Ag-ID8 has excellent stability and can be reused in photocatalysis experiments.